Hydroxytyrosol improves mitochondrial function and reduces oxidative stress in the brain of db/db mice: role of AMP-activated protein kinase activation. Issue 11 (17th April 2015) - Zheng, Adi; Li, Hao; Xu, Jie; Cao, Ke; Li, Hua; Pu, Wenjun; Yang, Ziqi; Peng, Yunhua; Long, Jiangang; Liu, Jiankang; Feng, Zhihui
Abstract : Hydroxytyrosol (HT) is a major polyphenolic compound found in olive oil with reported anti-cancer and anti-inflammatory activities. However, the neuroprotective effect of HT on type 2 diabetes remains unknown. In the present study, db/db mice and SH-SY-5Y neuroblastoma cells were used to evaluate the neuroprotective effects of HT. After 8 weeks of HT administration at doses of 10 and 50 mg/kg, expression levels of the mitochondrial respiratory chain complexes I/II/IV and the activity of complex I were significantly elevated in the brain of db/db mice. Likewise, targets of the antioxidative transcription factor nuclear factor erythroid 2 related factor 2 including p62 (sequestosome-1), haeme oxygenase 1 (HO-1), and superoxide dismutases 1 and 2 increased, and protein oxidation significantly decreased. HT treatment was also found to activate AMP-activated protein kinase (AMPK), sirtuin 1 and PPARγ coactivator-1α, which constitute an energy-sensing protein network known to regulate mitochondrial function and oxidative stress responses. Meanwhile, neuronal survival indicated by neuron marker expression levels including activity-regulated cytoskeleton-associated protein, N -methyl-d -aspartate receptor and nerve growth factor was significantly improved by HT administration. Additionally, in a high glucose-induced neuronal cell damage model, HT effectively increased mitochondrial complex IV and HO-1 expression through activating AMPK pathway, followed by the prevention of high glucose-induced production of reactive oxygen species and declines of cell viability and VO2 capacity. Our observations suggest that HT improves mitochondrial function and reduces oxidative stress potentially through activation of the AMPK pathway in the brain of db/db mice.